Some Higher Fungi from Sagarmatha National Park (SNP) and its Adjoining Areas, Nepal - Giri, Anjana; Rana, Prabina (Scientific World, 2010)
The present paper includes a list of 69 species of wild mushrooms collected from Sagarmatha National Park (SNP) and its adjoining areas, which are recorded for the first time from this area. Key words: Mushrooms; Mixed forest; Khumbu region. DOI: 10.3126/sw.v5i5.2659 Scientific World, Vol. 5, No. 5, July 2007 67-74